Hematological malignancy burden in mainland China and Taiwan from 1990 to 2021 and decadal projections: Insights from the global burden of disease study 2021. - Yu Fu; Ya-Zhe Du; Yun-Wei Zhang; Fei Song; Su-Jun Gao; Long Su (PLoS ONE)
Objectives Hematological malignancies (HMs) pose a severe threat to human health and contribute substantially to the disease burden in mainland China and Taiwan. Therefore, understanding their burden is crucial for informed decision-making and the effective allocation of healthcare resources. Methods This study utilized the latest data from the Global Burden of Disease 2021 study to describe the epidemiological indices of HMs in mainland China and Taiwan from 1990 to 2021. The future disease burden was projected for the next decade using the Bayesian age-period cohort (BAPC) model. Results Between 1990 and 2021, mainland China experienced an increase in the prevalence and incidence of leukemia and lymphoma, while the mortality and disability-adjusted life years (DALYs) for these diseases declined. Conversely, Taiwan witnessed an overall increase in the prevalence, incidence, mortality, and DALYs of leukemia over the same period. Additionally, multiple myeloma (MM), myelodysplastic/myeloproliferative neoplasms, and other hematopoietic neoplasms have shown significant increases in prevalence, incidence, mortality, and DALYs in China. While the disease burden of myeloid leukemia decreased in mainland China, that of lymphoid neoplasms (including leukemia, lymphoma, and MM) increased, which was not observed in Taiwan. Predictions from the BAPC model suggest that the incidence of several lymphoid neoplasms and MM is expected to increase in mainland China and Taiwan. Conclusions Taiwan continues to face greater challenges in managing HMs compared to mainland China. MM imposes a significant burden on the Chinese population. The findings of this study provide valuable epidemiological insights for optimizing the allocation of medical resources.